Investigation of the Effect of Urban Identity on Urban Landscape Design with Eye Tracking Technique in the Case of Konya City - Gemici, Ruhugül Özge; POLAT, AHMET TUGRUL (Selcuk journal of agriculture and food sciences (Online), 2023)
The aim of this study is to examine the effect of Konya urban identity on the urban landscape design of Konya city through eye tracking technique (method) through individuals. Within the scope of the research, first of all, a literature review on the subject was made. Afterwards, urban landscape areas with dense urban identity components determined in the light of literature resources were visited and photographs were obtained from these areas. Interviews were held with experts in the field of Konya urban identity, and as a result of these interviews, the photographs to be used in eye tracking analysis were determined. The photographs were uploaded to the eye tracking program and heat maps of the eye movements of the volunteer participants were created using the eye tracking device, and the numerical data (fixation numbers and fixation times) of the eye tracking analysis were reached. In addition, questionnaires were applied to the participants after the eye tracking analysis. As a result of the research, it was revealed that heat maps and eye tracking numerical data supported the questionnaires. Based on this, the conclusion that Konya’s urban identity has an effect on Konya's urban landscape design was reached through the people who participated in the study. The aim of this study is to examine the effect of Konya urban identity on the urban landscape design of Konya city through eye tracking technique (method) through individuals. Within the scope of the research, first of all, a literature review on the subject was made. Afterwards, urban landscape areas with dense urban identity components determined in the light of literature resources were visited and photographs were obtained from these areas. Interviews were held with experts in the field of Konya urban identity, and as a result of these interviews, the photographs to be used in eye tracking analysis were determined. The photographs were uploaded to the eye tracking program and heat maps of the eye movements of the volunteer participants were created using the eye tracking device, and the numerical data (fixation numbers and fixation times) of the eye tracking analysis were reached. In addition, questionnaires were applied to the participants after the eye tracking analysis. As a result of the research, it was revealed that heat maps and eye tracking numerical data supported the questionnaires. Based on this, the conclusion that Konya’s urban identity has an effect on Konya's urban landscape design was reached through the people who participated in the study.